ANALISIS PENGARUH FAKTOR MAKROEKONOMI DAN INDEKS GLOBAL TERHADAP INDEKS HARGA SAHAM GABUNGAN BURSA EFEK INDONESIA - Rosuliani Nurul Hidayah Setiana (2022)
Indonesia Composite Index is a stock index that describes the performance of stock in Indonesia as a whole. This study is a quantitative study that aims to determine the influence of macroeconomic factors and global indices on the Indonesia Composite Index in the long and short term. This study used data for the period 2017 to 2021. The method in this writing is the Error Correction Model (ECM) analysis method. The test results in this study are : (1) The BI Rate in the long term affects the composite stock price index while the short term does not affect on the Indonesia Composite Index (2) the foreign exchange rate (USD/IDR) has an influence on the long term and short term on the Indonesia Composite Index (3) inflation does not effect the long term and short term on the Indonesia Composite Index (4) The Dow Jones Industrial Average affects the Indonesia Composite Index in the long and short term.